Social representations of African descent: the cultural adventure, the sexual and gender violence and the multidimensional struggles - Meneses Copete, Yeison Arcadio; Universidad de Antioquia (Medellín, Colombia) (Pontificia Universidad Javeriana, 2014)
The women and men of African descent are represented socially as "objects of cultural adventure". There is a brand that uses gender and sexual-based violence exacerbated by the racialization of the body. It represents, objectifies and "cloisters" women of African descent into the categories of "hot bodies", "gusty", "strong": chained bodies. Since social representations shape human behavior and social practices, the discourses and imaginaries of men and women of African descent generate the "disposal" of the relations that they establish with mestizos and other human groups, including their co-ethnic bonds. Similarly, these representations make them more prone to sexual violence. For men, there is a continuity in the discourse of "virile male" that "discards", "objectifies" and, in turn, preforms a construction of masculinity, sexuality, sexual identity and the relationship with other sexualities. Such representations lead men and women to avoid being affectionate and close in their interactions with the same sex, with their couples and in their social and family relationships.